Inclusion of children identified as having special educational needs (SEN) within the Austrian compulsory educational system - Paleczek,Lisa (2015)
The present paper aims at describing various aspects of segregation, integration and inclusion within the Austrian compulsory school system. After a general introduction which includes definitions and a short international overview, the Austrian compulsory school system is described shortly. Subsequently, three subjects of interest are discussed. Firstly, the current situation of inclusion of children identified as having special educational needs (SEN) is characterized. This is very different in each one of the federal states, and the various developments which led to this situation are described. Secondly, recent empirical studies on the Austrian movement towards inclusion are shown in a brief overview. Thirdly, by way of example, recent developments, further plans and future visions of three federal states of Austria are presented in more detail.